2019
DOI: 10.3389/fnins.2019.01271
|View full text |Cite
|
Sign up to set email alerts
|

High-Salt Diet Causes Sleep Fragmentation in Young Drosophila Through Circadian Rhythm and Dopaminergic Systems

Abstract: Salt (sodium chloride) is an essential dietary requirement, but excessive consumption has long-term adverse consequences. A high-salt diet (HSD) increases the risk of chronic diseases such as cardiovascular conditions and diabetes and is also associated with poor sleep quality. Little is known, however, about the neural circuit mechanisms that mediate HSD-induced sleep changes. In this study, we sought to identify the effects of HSD on the sleep and related neural circuit mechanisms of Drosophila. Strikingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…The supplier reports that the AB152 successfully labeled TH in the striatum, sympathetic nerve terminals and adrenal glands. Staining of brain TH cells is significantly decreased in heterozygous TH‐knockout flies (Xie et al, 2019). In mice, AB152 was used in many studies for immunostaining of midbrain DA neurons in brain slices (e.g., Baron, Ratzka, & Grothe, 2012; Hennis, Seamans, Marvin, Casey, & Goldberg, 2013; Lobb, Zaheer, Smith, & Jaeger, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The supplier reports that the AB152 successfully labeled TH in the striatum, sympathetic nerve terminals and adrenal glands. Staining of brain TH cells is significantly decreased in heterozygous TH‐knockout flies (Xie et al, 2019). In mice, AB152 was used in many studies for immunostaining of midbrain DA neurons in brain slices (e.g., Baron, Ratzka, & Grothe, 2012; Hennis, Seamans, Marvin, Casey, & Goldberg, 2013; Lobb, Zaheer, Smith, & Jaeger, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Although the DASH sodium component was not significant in this study, it is recognized that high-salt diets can affect sleep quality. Xie et al found that young Drosophila on high-salt diet exhibit a fragmented sleep phenotype similar to that of normal aging individuals [69]. The induced sleep changes were attributed to impaired circadian rhythms and were dopaminergic system dependent [69].…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…Xie et al found that young Drosophila on high-salt diet exhibit a fragmented sleep phenotype similar to that of normal aging individuals [69]. The induced sleep changes were attributed to impaired circadian rhythms and were dopaminergic system dependent [69]. It is worth noting that approximately 10% of our selected sample were hypertensive with systolic blood pressure ≥150 mm Hg and/or diastolic blood pressure ≥90 mm Hg (7.2% in the 30-59 yo group; 20.1% in the 60+ yo group, P < 0.05, Wald test for age group difference), with no gender differences.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…Most people consume excessive amounts of salt-on average, about twice the maximum recommended amount [4]. An HSD can also negatively impact brain health, causing deficits in behavior and physiological processes such as cognitive function [5][6][7] and sleep [8,9]. However, how an HSD affects brain neuron function is still unclear.…”
Section: Introductionmentioning
confidence: 99%